PENGARUH KOMISARIS INDEPENDEN (KI), CORPORATE SOCIAL RESPONSIBILITY (CSR), INTELLECTUAL CAPITAL (IC) TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Yudhi Yuliansyah; Henik Hari Astuti; Yvone Augustine (Jurnal Magister Akuntansi Trisakti, 2017)
This study aims to determine the effect Idependent Commissioner, Corporate Social Responsibility, and Intellectual Capital on the variable value of the firm (PBV) in manufacturing companies during the period of the year from 2011 to 2015. The sample was selected by 34 companies manufacturing during 2011 to 2015. Data were analyzed using multiple regression analysis with Eviews version 9.0.The results showed that: Idependent Commissioner does not positive effect on the value of the firm(PBV), Corporate Social Responsibility does not positive effect on the value of the firm (PBV), and Intellectual Capital positive effect on the value of the firm (PBV).